Physiological differences between sprint- and distance-specialized cross-country skiers - Losnegard, T.; Hallén, J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: Sprint- (<1.8 km) and distance-skiing (>15 km) performance rely heavily on aerobic capacity. However, in sprint skiing, due to the ~20% higher speed, anaerobic capacity contributes significantly. This study aimed to identify the possible anthropometric and physiological differences between elite male sprint and distance skiers. Methods: Six sprint and 7 distance international-level cross-country skiers completed testing using the V2 skating technique on a roller-ski treadmill. Measurements included submaximal O2 cost (5°, 3 m/s) and a 1000-m time trial (6°, >3.25 m/s) to assess VO2peak and accumulated oxygen (SO2) deficit. Results: The groups displayed similar O2 cost during the submaximal load. The sprint skiers had a higher SO2 deficit (79.0 ± 11.3 vs 65.7 ± 7.5 mL/kg, P = .03, ES = 1.27) and VO2peak in absolute values (6.6 ± 0.5 vs 6.0 ± 0.5 L/ min, P = .04, ES =1.23), while VO2peak relative to body mass was lower than in the distance skiers (76.4 ± 4.4 vs 83.0 ± 3.2 mL/kg/min, P = .009, ES = 1.59). The sprint skiers were heavier than the distance skiers (86.6 ± 6.1 vs 71.8 ± 7.2 kg, P = .002, ES = 2.07), taller (186 ± 5 vs 178 ± 7 cm, P = .04, ES = 1.25), and had a higher body-mass index (24.9 ± 0.8 vs 22.5 ± 1.3 kg/m2, P = .003, ES = 2.05). Conclusion: The elite male sprint skiers showed different anthropometric and physiological qualities than the distance skiers, with these differences being directly related to body mass.